A novel gravity-driven nanofibrous membrane for point-of-use water disinfection: polydopamine-induced in situ silver incorporation - Wang, Jianqiang (2018)
We report a facile method for preparing silver-loaded membranes for point-of-use disinfection and disaster relief applications. A bio-inspired material, polydopamine, was coated onto a highly porous nanofibrous polyacrylonitrile substrate. We then take advantage of the redox properties of polydopamine to form silver nanoparticles in situ. These nanoparticles were uniformly distributed on the surface of nanofibers with no apparent agglomeration at a silver loading up to 4.36 wt.% (cPAN-Ag1.5). The silver-incorporated membrane cPAN-Ag1.5 achieved a high pure water flux of 130 Lm−2 h−1 at 10-cm water head, demonstrating the feasibility of energy-efficient gravity-driven filtration and eliminating the need for electrical power. The strong anti-bacterial activity and high physical rejection of the membrane led to an excellent disinfection power, with no viable bacterial cells detected in its permeate water. The membrane exhibited >7 log reduction for E. coli and >6 log reduction for B. subtilis. The strategy reported here provides an efficient and green route to synthesize point-of-use membranes. Combining their excellent permeability and disinfection effectiveness, these membranes offer an ideal solution to water supply in disaster-affected areas.